2018
DOI: 10.1097/md.0000000000011051
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic neuropathy and rhabdomyolysis after carbon monoxide intoxication

Abstract: Rationale:Peripheral neuropathy is a rare complication of carbon monoxide intoxication. Peripheral neuropathy following carbon monoxide intoxication is known to completely recover within a few months.Patient concerns:A 40-year-old man complained of motor weakness and hypoesthesia of the right lower extremity with swelling of his right thigh after carbon monoxide intoxication resulting from a suicide attempt.Diagnoses:Following nerve conduction and electromyographic studies, the patient was diagnosed with sciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…Atraumatic gluteal compartment syndrome (GCS) is rare occurrence, it is hypothesized that prolonged pressure due to resting on hard uneven surfaces in an unusual position can lead to gluteal muscles swelling and edema, resulting in increased intra-compartmental pressure [ 22 ]. This can occur in multiple conditions where the patient consciousness or orientation has been altered, such as drug abuse, alcohol intoxication, carbon monoxide poisoning, and surgical positioning [ 10 , [15] , [16] , [17] , [18] , 23 ]. Due to the large muscle mass GCS is frequently accompanied by crush syndrome, which describes systemic manifestations of rhabdomyolysis and multiple organ failure alongside compartment syndrome [ 3 , 11 , 12 , 14 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Atraumatic gluteal compartment syndrome (GCS) is rare occurrence, it is hypothesized that prolonged pressure due to resting on hard uneven surfaces in an unusual position can lead to gluteal muscles swelling and edema, resulting in increased intra-compartmental pressure [ 22 ]. This can occur in multiple conditions where the patient consciousness or orientation has been altered, such as drug abuse, alcohol intoxication, carbon monoxide poisoning, and surgical positioning [ 10 , [15] , [16] , [17] , [18] , 23 ]. Due to the large muscle mass GCS is frequently accompanied by crush syndrome, which describes systemic manifestations of rhabdomyolysis and multiple organ failure alongside compartment syndrome [ 3 , 11 , 12 , 14 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It usually leads to local muscle swelling, which may be the cause of increased the intra-compartmental pressure. This in turn will cause tissue hypo-perfusion and muscle necrosis and eventually rhabdomyolysis occurs, and patient might develop acute renal failure [ 17 , 18 ]. Peripheral neuropathy is a rare associated complication, and its prevalence has been reported to be 0.84% in 2360 patients diagnosed with Carbon monoxide intoxication [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhabdomyolysis is not generally associated with Kratom use, but there are numerous reports of opioids, sedativehypnotics, ethanol, and carbon monoxide resulting in prolonged periods of immobilization with rhabdomyolysis caused by pressure necrosis. [6][7][8][9][10] In a case series of 30 patients found down after opioid overdose, the authors suggested poor function on presentation did not improve despite fasciotomy. 11 Our case suggests the sedative effects of Kratom because of its action on the mu-receptor resulted in a similar case of pressure necrosis and compartment syndrome.…”
Section: Discussionmentioning
confidence: 99%